Evaluation of the USDA Fresh Fruit and Vegetable Program in Wisconsin Schools : Findings Following One Year of Implementation. - Glodowski, Kathryn R.; Lauersdorf, Brandon; Lutz, Beth (My University, 2009)
Previous research suggests that the Wisconsin Fresh Fruit and Vegetable Program (FFVP) has been effective in increasing student willingness to gry new fruits and vegetables served in schools after just three months of program implementation. This study tests various dimensions of the program in order to improve the effectiveness of the program.
Color poster with text and charts describing research conducted by Kathryn Glodowski, Brandon Lauersdorf, and Beth Lutz, advised by Lori A. Bica and Eric M. Jamelske.
Keywords: Fresh Fruit and Vegetable Program (Wis.); Nutrition--Study and teaching (Elementary)--Wisconsin; School children--Food--Wisconsin; School children--Nutrition--Wisconsin; Posters